Activating the desire to learn - Sullo, Robert A., 1951- (Virginia : Association for Supervision and Curriculum Development, 2007)
Theory and research. Understanding internal motivation -- "Where's the evidence?" -- Elementary school. Competition is as important as cooperation -- Helping students value learning -- From bossing to leading -- "Consequence" is not a four-letter word -- Middle school. Positive relationships support competence and high standards -- Self-evaluation leads to lasting change -- Inspiring through collaboration -- Being what we choose -- High school. Creating a need-satisfying environment -- From telling to asking -- From enforcing to teaching responsibility and fostering positive relationships -- Reflections of a high school senior.
Includes bibliography and index.
Keywords: Motivation in education; Learning; Motivation (Psychology); Achievement motivation in adolescence; Effective teaching